Beyond the "Jewish panel": the importance of offering expanded carrier screening to the Ashkenazi Jewish population - Shelley Dolitsky, M.D; Anjali Mitra, M.D; Shama Khan, M.P.H., M.S., L.C.G.C; Elena Ashkinadze, M.S., L.C.G.C; Mark V. Sauer, M.D., M.S (Elsevier, 2020)
Objective: To assess whether or not the current American College of Obstetricians and Gynecologists (ACOG) recommendations regarding carrier screening are sufficiently robust in detecting mutations in the Ashkenazi Jewish (AJ) population. Design: Cross-sectional study. Setting: Outreach program at university community center. Patient(s): Self-identified Jewish students, 18-24 years of age, interested in genetic carrier testing. Intervention(s): Expanded carrier screening (ECS) with the use of a commercially available targeted genotyping panel including >700 mutations in 180 genes. Main Outcome Measure(s): Gene mutations found in this population were grouped into three categories based on ACOG's 2017 committee opinion regarding carrier screening: category 1: the four commonly recommended genetic conditions known to be a risk for this population; category 2: 14 genetic disorders that should be considered for more comprehensive screening, including those of category 1; and category 3: the ECS panel, which includes category 2. Result(s): A total of 81 students underwent screening and 36 (44.4%) were ascertained to be carriers of at least one mutation. A total of 45 mutations were identified, as 8 students were carriers for more than one condition. If testing were limited to category 1, 84% of the mutations would not have been identified, and if limited to category 2, 55% of mutations would have gone undetected. Conclusion(s): Individuals of Ashkenazi Jewish descent are at significant risk for carrying a variety of single-gene mutations and therefore they should be offered panethnic ECS to increase the likelihood of detecting preventable disorders.